Factors Influencing Covid-19 Booster Decision Making among Elderly with Chronic Disease in Northeast Thailand - Intaranongpai Siranee; Kanetapilak Jarawee; Chatsupakul Jiraporn; Motam Sunipa (Jurnal Keperawatan Soedirman, 2026)
Little is known about the factors influencing elderly individuals’ decisions regarding the COVID-19 booster vaccine, especially given the ongoing evolution of the virus. This study aimed to determine the factors affecting decision-making about receiving the booster doses. A total of 597 participants were recruited through stratified random sampling for this analytical cross-sectional study conducted from August 2023. Research instruments included a questionnaires based on Protection Motivation Theory and intensions to receive the COVID-19 vaccine. Data were analyzed using descriptive statistics and multiple logistic regression. The results showed that the majority of participants were female (67.00%), aged over 66 years (64.32%), and single (72.22%). Notably, 72.22% hesitated to receive the third booster dose, and and 73.87% reported not receiving the booster due to fear of adverse events following immunization. Participants who were retired government officials or in other occupations (Adjusted OR = 3.142, 95% CI:1.938-8.294) had two co-morbidities (Adjusted OR = 4.637, 95% CI: 2.113-9.004), had high perceived severity (adjusted OR = 3.321, 95% CI: 1.943-9.625), had high self-efficacy (adjusted OR = 7.392, 95% CI: 1.042-12.634), and had high protection motivation (Adjusted OR = 6.832, 95% CI: 2.347-14.628) were significantly more likely to decide to receive the COVID-19 booster dose. Nurses should focus on promoting awareness and prevention of adverse effects related to the booster vaccine.